L’étude de la réflexivité en débriefings dans le cadre du programme du cours d’action - Gilles Dieumegard; Nicolas Perrin; Frédéric Brissaud (Activités)
While reflexivity has become central to the fields of professional training and learning, it has not been a central focus in the research conducted during the course of action program. In studying the experience of debriefing in psychotherapy training, we focused on “reflexive practices” of returning in the present to a past moment of activity. To achieve this, we used the enactive concept of “distinction” and developed the related notions of remanent structures and narrative and conceptual chains. This allowed us to define different types of "remembering", the retrieval in the present of moments of past experience. The results show, during the debriefing, a circulation between the different forms of construction of remanent structures and of remembering, as well as a multi-temporality of the experience which does not reduce it to the temporal horizons of the debriefing and of the analysed situation. These results open up the debriefings to objectives and temporalities broader than those usually assigned to them. Furthermore, the enrichment of the theoretical and analytical framework of the course of action program allows us to address reflexivity, abstraction and conceptualisation, and thus to better identify what brings it closer to or differentiates it from professional didactics.